Wyniki ekonomiczne gospodarstw utrzymujących bydło simentalskie na Podkarpaciu - Kusz, Dariusz; Stec, Artur (Economic Results of the Farms Breeding Simmental Cattle in the Region of Podkarpacie, 2006)
It has been found that together with the increase in the number of cows, the higher level of agricultural income is achieved. The level of income is influenced by direct subsidies. Together with the increase in the head age of cows on the farms, the profitability of land and work also significantly increased, which may reflect the fact that economic results and effectiveness depend on the ability to use scale economics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 520-524